Discovering scientific measure of commuting graph in co-authorship network using centrality analysis / Ahmad Mirza Ahmad Taif, Amirul Faiz Azizul Fatah and Fazreena Izzati Mohammad Isa - Ahmad Taif, Ahmad Mirza; Azizul Fatah, Amirul Faiz; Mohammad Isa, Fazreena Izzati (2023)
Study of social networks reveal communication patterns which are of interest to researchers. A co-authorship network is one type of a social network. These networks represent the publication work carried out by researchers. Researchers have poured attention into diverse within social networks. Co-authorship networks analysis is useful in understanding the structure of scientific collaborations and status of individual authors. Centrality measure calculation is one of the many tasks of social network analysis. The focus of this project is on measuring the centrality analysis on the co-authorship network using a social network analysis tool, UCINET and visualizing the co-authorship network using VOS viewer. Results of this findings is the top 10 ranked authors based on their centrality measure in the co-authorship network.